2014
DOI: 10.1139/cjpp-2013-0168
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of escitalopram and atorvastatin on diet-induced atherosclerosis in rats

Abstract: Atherosclerosis is one of the most common disorders among the elderly. Depression may be associated with the development of atherosclerosis. Thus, the aim of this study is to evaluate and compare the effects of escitalopram (a selective serotonin reuptake inhibitor) with atorvastatin (a well known antihyperlipidemic drug) on high fat diet induced atherosclerosis in rats. The results of this study showed that the administration of either escitalopram or atorvastatin for 6 weeks was associated with a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 49 publications
7
11
1
Order By: Relevance
“…These results were consistent with previous findings [13][14][15][16][17][18][19][20] and further supported the concept of the pleiotropic vascular protection effects of atorvastatin in hypercholesterolemia. Atorvastatin treatment caused a decrease in MDA, whereas the high-cholesterol diet increased MDA of blood and heart tissue in cholesterol-rich diet-induced rabbits.…”
Section: R E S U L T Ssupporting
confidence: 93%
See 1 more Smart Citation
“…These results were consistent with previous findings [13][14][15][16][17][18][19][20] and further supported the concept of the pleiotropic vascular protection effects of atorvastatin in hypercholesterolemia. Atorvastatin treatment caused a decrease in MDA, whereas the high-cholesterol diet increased MDA of blood and heart tissue in cholesterol-rich diet-induced rabbits.…”
Section: R E S U L T Ssupporting
confidence: 93%
“…The possible antihypercholesterolemia mechanism of atorvastatin may regulate the disorder of lipid metabolism as well as enhance cardiac function. These results were consistent with previous findings [13][14][15][16][17][18][19][20] and further supported the concept of the pleiotropic vascular protection effects of atorvastatin in hypercholesterolemia. In the presence of atherogenesis or risk factors such as hypercholesterolemia, NO levels are decreased [21].…”
Section: R E S U L T Ssupporting
confidence: 93%
“…Studies in rodents have shown that SSRIs reduce atherosclerotic changes in the endothelium as measured by decreased expression in cell adhesion molecules (VCAM-1) 45 . In humans, a randomized clinical trial demonstrated that patients with congestive heart failure taking sertraline, an SSRI, had a reduction in the expression of cell endothelial adhesion molecules (VCAM and ICAM) after a 3 month exposure compared to patients receiving placebo indicating a possible anti-inflammatory effect 46 .…”
Section: Discussionmentioning
confidence: 99%
“…It is peripheral arterial disease (PAD), most prevalent, morbid, and mortal disease [ 9 ]. It is one of the most common disorders among the elderly, because of depression prevailed in the old age and rates of very high atherosclerosis [ 10 ]. Atherosclerosis is characterized by endothelial dysfunction, vascular inflammation, and the buildup of lipids, cholesterol, calcium, and cellular debris within the intima of the walls of large and medium size arteries [ 11 ].…”
Section: Introductionmentioning
confidence: 99%